The Analysis of Service Integrity on Video Streaming Services Using Time Division Duplex and Frequency Division Duplex Technology on LTE Networks - Chandra, Dikky; Yusnita, Sri; Sitepu, Dana Bahari; Rusfandi, -; Meidelfi, Dwiny (SOTVI, 2021)
The growing use of cellular technology has a rapid impact on the development of technology and information. This development relates to the use of information and communication services that is tailored directly, practically and effectively manner. Responding to the issue, the researcher is interested in conducting research by looking at the parameters using Time Division Duplex (TDD) technology and Frequency Division Duplex (FDD) technology on video streaming services. Service integrity measurement results on LTE networks are carried out in real time in the field according to the research path and eNodeB installed in dedicated mode. Dealing with the results, the effect of DT parameters on service integrity can only be seen in the SINR and CQI parameters. When SINR measured 21.3 dB and CQI measured 13.5, the measured throughput was 3665.2 Kbps so that the measured modulation was 64 QAM, on the other hand, if SINR measured -0.2 dB and CQI measured 10, the measured throughput was 0.5 Kbps so that the modulation measured was small, namely QPSK. From the results obtained, LTE TDD has a better service integrity value, namely throughput has a value of 891.16 Kbps and a latency of 48 ms for Telkomsel while 882.14 Kbps and latency was 49 ms for Smartfren than LTE FDD which had a throughput value of 820.83 Kbps and a latency was 68 ms for Telkomsel while 831.21 Kbps and 77 ms latency were for Smartfren, thus LTE TDD is better in terms of throughput and measured latency.